AB0690 Pulmonary arterial hypertension (PAH) in a cohort of systemic lupus erythematosus (SLE). (23rd January 2014) - Bianchi, M.M.; Santo, P.; Estrada, P.; Lόpez, L.; Aparicio, M.; Narváez, J.; Valverde, J.; Nolla, J.
Abstract : Background: PAH is a rare complication of SLE and the prevalence varies among the different studies and diagnostic method employed. The clinical course of PAH is asymptomatic until advanced stages and therefore has poor outcome (1). Objectives: The aim of this study is to estimate the prevalence of PAH in a cohort of SLE patients and evaluate if Raynaud's phenomenon (RP) and certain antibodies constitute risk factors for developing PAH. Methods: Asymptomatic SLE patients (who fulfilled ACR criteria for SLE) were recruited in a rheumatology unit of a hospital in Barcelona, Spain. We assessed clinical features of SLE, presence of antiphospholipid syndrome, interstitial lung disease, pulmonary embolism, autoantibody profile and history of RP. Transthoracic echocardiography (TTE) was performed to all SLE patients to estimate the pulmonary artery pressures. PAH was defined as systolic pulmonary artery pressure (sPAP) ≥36 mmHg according to current guidelines (2). Results: 49 SLE patients were evaluated with TTE and none had PAH. We separated two groups according to sPAP ≤30 and sPAP between ≥31 to 35 mmHg; not finding any differences between the clinical features of the 2 groups. Conclusions: PAH is a serious complication with very low prevalence in SLE patients. In our SLE cohort none of our patients developed PAH. Also, we failed to prove any association with RP in the group with higher sPAP. Finally, with our study we may conclude that routine screening with TTE in asymptomatic SLE patients is not justified due to the very low prevalence of PAH in our SLE population. References: Sánchez O, Sitbon O, Jaïs X, Simonneau G, Humbert M. Immunosuppressive therapy in connective tissue diseases-associated pulmonary arterial hypertension. Chest 2006; 130:182-9. Galiè N, Torbicki A et al. Guidelines on diagnosis and treatment of pulmonary arterial hypertension. The Task Force on Diagnosis and Treatment of Pulmonary Arterial Hypertension of the European Society of Cardiology. Eur Heart J. 2004; 25:2243-78. Disclosure of Interest: None Declared